Regulating the phase distribution of quasi-2D perovskites using a three-dimensional cyclic molecule toward improved light-emitting performance. Issue 46 (16th November 2022) - Chen, Chiung-Han; Hsu, Chiao-Hsin; Ni, I-Chih; Lin, Bi-Hsuan; Wu, Chih-I.; Kuo, Chi-Ching; Chueh, Chu-Chen
Abstract : A cage-like cryptand acts as an effective additive for quasi-two-dimensional (quasi-2D) perovskites, not only to improve the quality of the film but also to modulate its phase distribution and promote cascade energy transfer between multiphase. Abstract : In this study, a molecule with a three-dimensional (3D) cyclic structure, a cryptand, is demonstrated as an effective additive for the quasi-two-dimensional (quasi-2D) PEA2 Cs n −1 Pb n Br3 n +1 ( n = 3, herein) to improve its light-emitting performance. The cryptand can effectively regulate the phase distribution of the quasi-2D perovskite through its intense interaction with PbBr2, benefitting from its cage-like structure that can better capture the Pb 2+ ions. Due to the inhibited growth of the low- n phases, a much-concentrated phase distribution is achieved for the cryptand-containing films. Moreover, its constituent O/N atoms can passivate the uncoordinated Pb 2+ ions to improve the film quality. Such a synergistic effect thereby facilitates the charge/energy transfer among the multiple phases and reduces the non-radiative recombination. As a result, the quasi-2D perovskite light-emitting diode (PeLED) with the optimized cryptand doping ratio is shown to deliver the highest luminance ( L max ) of 15 532 cd m −2 with a highest external quantum efficiency (EQE) of 4.02%. Compared to the pristine device, L max is enhanced by ∼5 times and EQE is enhanced by ∼10 times.